Penerapan Sanksi Pidana Denda Sebagai Upaya Menekan Tingkat Pelanggaran Lalu Lintas di Kota Ternate - Sudarsono, M. Agus F; Malik, Faissal; Anshar, Anshar (Faculty of Law, Khairun University, 2020)
The legal basis regulating traffic is Law of the Republic of Indonesia Number 22 of 2009 concerning